2019
DOI: 10.1038/s41467-019-09720-x
|View full text |Cite
|
Sign up to set email alerts
|

KIBRA controls exosome secretion via inhibiting the proteasomal degradation of Rab27a

Abstract: Exosomes are nanosized membrane vesicles released from cells after fusion of multivesicular bodies (MVBs) with the plasma membrane (PM) and play important roles in intercellular communication and numerous biological processes. However, the molecular mechanisms regulating exosome secretion remain poorly understood. Here we identify KIBRA as an adaptor-like protein that stabilizes Rab27a, which in turn controls exosome secretion both in vitro and in vivo. Knockdown or overexpression of KIBRA in neuronal and podo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(139 citation statements)
references
References 50 publications
6
133
0
Order By: Relevance
“…Firstly, we identified that exosome secretion increased significantly via IRF-1/Rab27a in TECs as the initial adaptive response to albumin overload, and KIBRA might participated in stabilizing of Rab27a as reported before 29 . Previous studies have suggested that stress conditions, such as hypoxia, proteinuria increased exosomes release from renal TECs 14,20 , while the underlying mechanisms remain unclear.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Firstly, we identified that exosome secretion increased significantly via IRF-1/Rab27a in TECs as the initial adaptive response to albumin overload, and KIBRA might participated in stabilizing of Rab27a as reported before 29 . Previous studies have suggested that stress conditions, such as hypoxia, proteinuria increased exosomes release from renal TECs 14,20 , while the underlying mechanisms remain unclear.…”
Section: Discussionsupporting
confidence: 53%
“…5f). Considering that KIBRA has been proven as an adaptor-like protein to prevent Rab27a from ubiquitination for degradation in kidney 29 , KIBRA siRNA was transfected in TECs to investigate the role of KIBRA in Rab27a expression. Knockdown of KIBRA attenuated upregulation of Rab27a protein in TECs exposed to albumin ( Supplementary Fig.…”
Section: Interferon Regulatory Factor 1 (Irf-1) Is Induced As the Tramentioning
confidence: 99%
“…Since their original description over 30 years ago, exosomes are now known as a subtype of extracellular vesicles (EVs) with the size range 50–150 nm and can be harvested from cell culture or isolated from patient's body fluids which can be subsequently modified in vitro and transferred back to the same patient . Exosomes are released from cells upon fusion of multivesicular body with the plasma membrane, different from microvesicles, which are formed and released by budding from the plasma membrane of cells . Apart from exosomes and microvesicles, the nomenclature of EVs also includes microparticles, ectosomes, oncosomes, and apoptotic bodies .…”
Section: Introductionmentioning
confidence: 99%
“…23 Our recent study showed that kidney and brain protein (KIBRA), an adaptor-like protein, can regulate the secretion of exosomes through a Rab27A-dependent mechanism, and participate in the progression of AD pathology. 24,25 Another of our recent studies indicated that the up-regulation of mammalian target of rapamycin (mTOR) facilitates the release of tau into the extracellular space in an exosome-independent manner in SH-SY5Y cells. 26 More recently, research has shown that the mTOR complex 1 (mTORC1) also regulates the release of exosomes through a Rab27A-dependent mechanism.…”
Section: Exosomesmentioning
confidence: 99%